SBF-1 inhibits contact hypersensitivity in mice through down-regulation of T-cell-mediated responses - Wei Chen; Xianying Fang; Yuan Gao; Ke Shi; Lijun Sun; Biao Yu; Qiong Luo; Qiang Xu (BMC, 2019)
Abstract Background T lymphocytes play an important role in contact hypersensitivity. This study aims to explore the immunosuppressive activity of SBF-1, an analog of saponin OSW-1, against T lymphocytes in vitro and in vivo. Methods Proliferation of T lymphocytes from lymph nodes of mice was determined by MTT assay. Flow cytometry analysis was performed to assess T cell activation and apoptosis. Levels of cytokines were determined by PCR and ELISA. BALB/c mice were sensitized and challenged with picryl chloride and thickness of left and right ears were measured. Results SBF-1 effectively inhibited T lymphocytes proliferation induced by concanavalin A (Con A) or anti-CD3 plus anti-CD28 at a very low dose (10 nM) but exhibited little toxicity in non-activated T lymphocytes at concentrations up to 10 μM. In addition, SBF-1 inhibited the expression of CD25 and CD69, as well as he phosphorylation of AKT in Con A-activated T cells. SBF-1 also induced apoptosis of activated T cells. In addition, SBF-1 also downregulated the induction of the T cell cytokines, IL-2 and IFN-γ in a dose-dependent manner. Furthermore, SBF-1 significantly suppressed ear swelling and inflammation in a mouse model of picryl chloride-induced contact hypersensitivity. Conclusions Our findings suggest that SBF-1 has an unique immunosuppressive activity both in vitro and in vivo mainly through inhibiting T cell proliferation and activation. Its mechanism appears to be related to the blockage of AKT signaling pathway.